Vertical Transmission at the Pathogen-Symbiont Interface: Serratia symbiotica and Aphids - Julie Perreau (American Society for Microbiology, 2021)
Insects have evolved various mechanisms to reliably transmit their beneficial bacterial symbionts to the next generation. Sap-sucking insects, including aphids, transmit symbionts by endocytosis of the symbiont into cells of the early embryo within the mother’s body.